An Analytical Study of the Impacts of Optimism on Urdu Poetry: رجائیت اور اس کے اردو شاعری سے متعلقہ کام پر اثرات تجزیہ - Anum, Tayiba (Al Khadim Research Journal of Islamic Culture and Civilization, 2023)
Optimism has its own characteristic in Urdu poetry and basically it reflects the positive aspects that poets use in their poetry to improve values. Various poets in their own style convey the message of changing social degradation and despair through determination and better thinking. They nurture the thinking of hope so that the social and moral values ​​can be improved. As far as poetry and literature are concerned, seeing the bright side of things and events and having an optimistic view about the future is called optimism, and a person whose thoughts are optimistic is called optimism. Or he has some extraordinary power, he is formed by the environment or the environment is formed by his writing. Do they influence or not, if they influence it, how much is the real thing that gives life to literature?